Kesiapan dan Penerimaan Karyawan terhadap Penerapan Lean Management di Rumah Sakit Bethesda - Katherina Adisaputro; Andreasta Meliala (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2021)
ABSTRACTIntroductions: Efficiency of health care services at a hospital became one of the solutions amid national health insurance era. Particular method offering the solution is lean management. Bethesda Hospital began implementing lean management in 2019. During the course of the program, readiness and acceptance evaluation at the level of employee never been accomplished. Organizations focused mainly on lean tools and lean techniques tend to allocate minimal measurement on readiness lead to reduced level of sustainability and last for short-term activities. Successful lean management require both preparation and implementation combining on lean readiness and lean acceptance data from the organization. Aim:This study aimed to measure employee readiness and acceptance toward implementation of lean management,and to describe the output of lean implementationMethods: An explanatory research took place in Bethesda Hospital, Yogyakarta. Survey were used to collect quantitative data while the qualitative approach performed through in-depth interviews.Results and Discussion: Lean readiness at Bethesda Hospital were analyzed using fuzzy and Euclidean. The analysis indicate value of 6.08 with HLR 4 distance 2.016 interpreted as